Pengaruh Kerjasama Tim terhadap Kinerja (Studi Pada Karyawan UD Gerald Unedo Putra Di Bangkalan) - Syor Yani; Iriani Ismail (Management Department of Economics and Business Of Trunojoyo Madura University, 2021)
The objectives of this study are to determine 1) the responsibility has a positive and significant effect on employees performance, 2) the mutual contributions has a positive and significant effect on employees performance, 3) the ability has a positive and significant effect on employees performance, 4) the responsibility, mutual contributions, and ability have effect on employees performance simultaneously, and 5) the variable that effect dominantly on employees performance. Based on the multiple linear regression analysis, the results showed that the responsibility has a positive and significant effect on employees performance with a standardized coefficients beta value is 0.57, mutual contributions has a positive and significant effect on employees performance with a standardized coefficients beta value is 0.707, the ability has a positive and significant effect on employees performance with a standardized coefficients beta value is 0.475. Simultaneously, the responsibility, mutual contribution, and ability have significant effect on employees performance with a significant level is 56,8%. Then, mutual contributions has effect dominantly on employees performance with a value is 0.388.